LOCAL TAXES BETWEEN OBLIGATION AND FISCAL CITIZENSHIP: Received: 29th April 2021; Revised: 22nd July 2021, 20th November 2021, 02nd December 2021; Accepted: 31st December 2021 - Sandu, Dorina (PEOPLE: International Journal of Social Sciences, 2022)
The fiscal compliance of the taxpayer reported in percentages regarding the realization of the receipts exceeds in meaning the payment of an obligation established at the level of fiscal policy. As an individual or an entity, the citizen-taxpayer transfers sums of money in the form of tax, but this transfer has in addition to the historical-economic-legislative component and a defining psycho-social one for what we call fiscal citizenship. Visible only in the voluntary fulfilment of fiscal obligations, less in positive attitudes and beliefs, perceptions, motivation, and trust in local authorities, fiscal citizenship remains the barometer of the citizen-public administration or public service relationship. Fiscal citizenship and its defining elements can indicate the extent to which citizens feel defended by democracy and the rule of law. It cannot strengthen fiscal citizenship without strengthening trust in public authorities in terms of fiscal policy and taxation, without the responsibility for the efficient use of the amounts collected, without considering the taxpayer in a threefold way: partner, beneficiary, and client of the local public tax service. A culture based on rights and responsibilities or the reciprocity of responsibility and the empowerment of the citizen-taxpayer is needed.